Arrow-Shot Injury to Pediatric Spinal Cord - Singh, Vijayveer; Thanvi, Sharad (Indian Journal of Neurotrauma, 2021)
Penetrating spinal cord injuries (PSCI) in cervical region are extremely rare in pediatric population. Most injuries in pediatric population are accidental due to gunshot or a stab injury with a sharp or pointed object. Gun shots may result into a severe wound which is usually fatal and may result in death, quadriplegia, or serious long-term disability. Stab injuries are less severe and may result in neurological sequalae. In this paper, an unusual case of pediatric arrow shot partial cervical cord injury is reported which was managed by aggressive neurosurgical management. The arrow lodged in the cervical cord was very near to the vertebral artery leading to parapariesis which recovered well without any complications. Diagnostic imaging at admission included radiographs, computed tomography (CT), and CT angiography of the cervical region. The patient underwent early surgical intervention with removal of foreign body from the cord and subsequent dural suturing.
Keywords: Brown–Sequard syndrome; cervical spinal cord; hemilaminectomy; methylprednisolone; pediatric population